Efeitos de doses de narasina sobre o desempenho, comportamento ingestivo, caracteristicas de carcaça e morfometria ruminal e cecal de bovinos Nelore confinados - Silva, Leandro Aparecido Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
O estudo foi realizado no confinamento experimental da Faculdade de Ciências Agrarias e Tecnológica – Unesp, Campus de Dracena, com o objetivo de avaliar os efeitos dos níveis de narasina em dietas de confinamento sobre o desempenho, características de carcaça, comportamento alimentar e morfometria ruminal e ceco de bovinos Nelore. O delineamento experimental foi em blocos inteiramente casualizados (128 bovinos Nelore, com peso vivo (PV) de 400 kg, alocados aleatoriamente em 32 baias n = 4 por baía). Neste estudo, os animais passaram por uma adaptação em escadas, sendo as dietas de adaptação 1(5 dias), 2 (4 dias) e 3 (5 dias) contendo 75, 79, 83% de concentrado, e na dieta de terminação(final) contendo 87% de concentrado. O tratamento foi dividido; 1) Trt 1. 0 ppm de Narasina (controle) ; 2) Trt 2. 13 ppm de Narasina; 3) Trt 3. 20 ppm de Narasina; 4) Trt 4. 27 ppm de Narasina. Em relação ao PV aos 28 dias de estudo, houve um efeito linear crescente (P = 0,02), em que PVaumentou à medida que a inclusão de Narasina na dieta foi aumentada, o que favoreceu bovinos que consumiram dietas com 27 ppm de Narasina. No tocante aos resultados de consumo de matéria seca (CMS), foi observado efeito quadrático (P ≤ 0,05) no período de 0 a84 dias, 0 a 111 dias, em que bovinos que receberam as doses de 13 e 20 ppm apresentaram as maiores CMS. Similares resultados foram observados para a CMS expressa em % do PV (P ≤ 0,05), a suplementação com Narasina resultou em um efeito quadrático nos valores para CMS (% PV) aos 0 a 84 dias e 0 a 111 dias, mostrando que a dosagem de 13 e 20 ppm apresentaram maiores CMS nesses intervalos. Já os efeitos das diferentes doses de Narasina sobre o ganho de peso diário (GPD), houve efeito linear crescente (P = 0,01), em que o GPD aumentou à medida que a inclusão de Narasina na dieta foi aumentada nos intervalos de 0 a 28 dias, favorecendo bovinos que consumiram dietas com 27 ppm de Narasina. Já a eficiência alimentar (EA), houve efeito linear crescente (P = 0,03), em que a EA melhorou no período de 0 a 28 dias, conforme aumento dos teores de Narasina na dieta experimental, o que resultou em melhoria na EA para os animais que receberam dietas com 27 ppm de Narasina. Em relação ao comportamento animal, foi observado efeito cúbico para tempo de alimentação por refeição (P = 0,05) onde animais que receberam dietas contendo 20 ppm de Narasina apresentaram os maiores valores. Foi observado efeito quadrático (P = 0,03) para consumo de matéria seca (CMS) em resposta a doses de 13 e 20 ppm de Narasina. Foi observado efeito quadrático para altura das papilas (P=0,02) e cubico para largura (P=0,03), sendo que animais que receberam doses de 13 ppm de narasina tiveram um efeito no crescimento das papilas e largura das papilas. A medida que se aumentou a dose de Narasina, foi observado redução linear (P = 0,01) do número de células de Goblet, totais e rompidas, assim como aumento linear (P = 0,03) da relação profundidade de cripta/células de Goblet. Desta forma, as doses de 20 ppm de Narasina podem ter reduzido a acidificação cecal e/ou favorecido a digestão dos nutrientes em compartimentos anteriores, resultando em ganhos de carcaças.

The study was conducted in the experimental confinement of the Faculty of Agricultural and Technological Sciences – FCAT, Unesp, Dracena Campus with the objective of evaluating the effects of narasin levels in confinement diets on performance, carcass characteristics, feeding behavior and ruminal morphometry. and cecum of Nellore cattle. The experimental design was in entirely cazualized blocks, in which 128 18-month-old Nelore cattle, not castrated, randomly allocated to 32 pens (n = 4 per bay), with an initial average live weight (BW) of 400.00 ± kg . In this study, the animals underwent a step-up adaptation, that is, three adaptation diets were provided, starting with 75% concentrate with increases of 4% between them, with the amount of roughage removed being in its entirety of hay. The transition from adaptation diets to finishing diets was made as follows: 5 days of adaptation 1, 4 days of adaptation 2 (79% concentrate) and 5 days of adaptation 3 (83% concentrate). The finishing diet was composed of 87% concentrated ingredients and the treatments were divided; 1) Trt 1. 0 ppm Narasin (control); 2) Trt 2. 13 ppm of Narasin; 3) Trt 3. 20 ppm Narasin; 4) Trt 4. 27 ppm of Narasin (Zimprova™; Elanco Saude Animal, São Paulo, SP). In relation to PV at 28 days of study, an increasing linear effect (P = 0.02) was observed, in which PV increased as the inclusion of Narasin in the diet was increased, which favored cattle that consumed diets with 27 ppm from Narasin. However, no other differences regarding PV were detected on the subsequent measurement days, including the measurement carried out at the end of the study on day 111. Regarding the IMS results, a quadratic effect was observed (P ≤ 0.05) in the period from 0 to 84 days, 0 to 111 days, in which cattle that received doses of 13 and 20 ppm presented the highest DMI. Similar results were observed for DMI expressed as % of BW (P ≤ 0.05), where supplementation with Narasin resulted in a quadratic effect on the values for DMI (% BW) at 0 to 84 days and 0 to 111 days, showing that the dosage of 13 and 20 ppm showed higher DMI in these intervals. Regarding the effects of different doses of Narasin on GPD, there was an increasing linear effect (P = 0.01), in which GPD increased as the inclusion of Narasin in the diet was increased in the intervals from 0 to 28 days, the which favored cattle that consumed diets with 27 ppm of Narasin. Regarding feed efficiency, there was an increasing linear effect (P = 0.03), in which feed efficiency improved in the period from 0 to 28 days, as Narasin levels increased in the experimental diet, which resulted in better feed efficiency for animals that received diets with 27 ppm of Narasin. Regarding animal behavior, a cubic effect was observed for feeding time per meal (P = 0.05) where Nelore cattle that received diets containing 20 ppm of Narasin showed the highest values. A quadratic effect (P = 0.03) was observed for DM consumption in response to doses of 13 and 20 ppm of Narasin. When a quadratic effect was observed for the height of the papillae (P=0.02) and a cubic effect for the width (P=0.03), the animals that received a dosage of 13 ppm of narasin had an effect on the growth of the papillae and the width of the papillae. These variables show that these animals had a more developed ruminal epithelium, compared to the other treatments. As the dose of Narasin was increased, a linear reduction (P = 0.01) in the number of total and ruptured Goblet cells was observed, as well as a linear increase (P = 0.03) in the crypt depth/cells ratio. by Goblet. Therefore, doses of 20 and 27 ppm of Narasin may have reduced cecal acidification and/or favored the digestion of nutrients in anterior compartments. Based on these results, narasin has positive effects on the productive performance of Nellore cattle in confinement. The main positive effects detected in the work are the increase in DM intake for cattle fed with 20 ppm of Narasin, in addition to the fact that animals that consumed 20 ppm of Narasin took longer to consume a meal, but even so without affecting the consumption of DM as a whole, therefore, Nelore cattle that received 20 ppm showed greater fat deposition in the sirloin, which may be the result of greater ruminal stability due to slower DM consumption. Furthermore, doses of 20 ppm contributed to protecting the cecum against acidification, which is positive, as nutrients may have been better digested in anterior compartments.
Effects of narasin doses on performance, ingestive behavior, carcass characteristics and ruminal and cecal morphometry of confined Nellore cattle
Keywords: Histologia; Ionóforo; Morfologia; Papilas; Rúmen